Automated VHF Radiotelemetry Revealed Site-Specific Differences in Fall Migration Strategies of Semipalmated Sandpipers on Stopover in the Gulf of Maine - Holberton, Rebecca L.; Taylor, Philip D.; Tudor, Lindsay M.; O'Brien, Kathleen M.; Mittelhauser, Glen H.; Breit, Ana (Frontiers in Ecology and Evolution, 2019)
The Gulf of Maine has long been recognized as a major stopover area for shorebirds in fall. Knowing how birds move within and beyond the region will be paramount to protecting threatened shorebird habitat. To determine stopover behavior during fall migration (2013-2017) in Maine, 180 (104 AHY, 76 HY) Semipalmated Sandpipers, Calidris pusilla, were tracked using VHF radiotelemetry and an extensive array of automated receivers (Motus Wildlife Tracking System). Birds tagged at three locations along the Maine coastline showed no effect of age class or stopover site on body condition (body mass, estimated fat mass) or stopover length (post capture detection period). However, movement after departure varied greatly among sites. Few birds captured at the northern-most site (“Downeast”, n=71), which had the greatest amount of mudflats and offshore roost sites and the least amount of human disturbance, were detected beyond the initial tagging location, suggesting that they, like birds in the Bay of Fundy just to the north, initiated trans-oceanic flights from that location. At the Downeast site, leaner birds remained significantly longer than fatter birds, suggesting that time of departure there depended on energy reserves, which would be critical for making extensive flights. In contrast, over half of the birds tagged further south (Popham Beach, n= 59; Rachel Carson NWR, n = 50) were later detected at coastal locations to the north (few) or to the south (most). Stopover period at these sites was independent of fat, suggesting that other factors (e.g. feeding/roosting site availability, human activity) influenced departure decisions. In Maine, Semipalmated sandpipers, regardless of age, may move north (Downeast) or south (e.g. Cape Cod, Rhode Island, Long Island Sound) where the local topography, habitat characteristics (feeding/roosting sites), and/or lower human activity, may best enable them to initiate trans-oceanic flights to the wintering grounds. Future study should determine if variation in stopover behavior is population-specific and if population-segregation occurs in Maine. Use of automated VHF radiotelemetry has lead to a greater understanding of stopover behavior and the degree of connectivity among stopover sites, which should be taken into account for conserving migratory bird habitat across broad spatial scales.